Reviews - Robin Shaw; Harish Ravat; Eleri Jones; Richard Storer; Bruce Douglas Ingraham; Sheila Stone; Ray McAleese; Erica McAteer; Philip Barker; Robert Ward (Association for Learning Technology, 1997)
This is the latest in a series of practical books published by Kogan Page in the field of education by Professor Phil Race in collaboration with various others. Phil Race, Emeritus Professor of Educational Development at the University of Glamorgan, has had a varied and inspirational career in higher education, and at present is Programme Director for the University of Durham Certificate in Teaching in Higher Education. Steve McDowell lectures in IT at Gateshead College and the Open University